2022
DOI: 10.24018/ejedu.2022.3.5.440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Activity-Based Learning on Basic Science and Technology Students’ Non-Cognitive Skills in South-South Nigeria

Abstract: This study investigated the Basic Science and Technology (BST) students’ reaction to the use of the Activity-Based Learning (ABL) approach, recently introduced by the Nigeria Universal Basic Education Commission (UBEC) in Primary schools; and the influence of the ABL approach has on the BST students’ non-cognitive outcomes. The study used a survey and posttest only quasi-experimental design. Three research questions and two hypotheses guided it. The study population was 2,800 BST students of the 56 teachers wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The ABL approach has proved to improve both cognitive and non-cognitive skills in children. Nwosu et al (2022) in a similar study found that the ABL approach improved students' non-cognitive skills, especially meta-cognitive abilities.…”
Section: Discussion Of Findingsmentioning
confidence: 77%
“…The ABL approach has proved to improve both cognitive and non-cognitive skills in children. Nwosu et al (2022) in a similar study found that the ABL approach improved students' non-cognitive skills, especially meta-cognitive abilities.…”
Section: Discussion Of Findingsmentioning
confidence: 77%
“…The social aspect of air pollution should be discussed in early classes where all the students follow a similar syllabus. The experts also suggested to include activity-based learning (Nwosu et al, 2022) and information regarding adaptations measures in personal life such as improved ventilation, behavioral modifications, and usage of clean cooking fuel in early classes (Gunnarsen & Fanger, 1992;Liao et al, 2021).…”
Section: Recommendationmentioning
confidence: 99%
“…Basic science and technology subjects play a pivotal role in shaping a child's understanding of the world, fostering critical thinking skills, and preparing them for the challenges of the modern era (Azonuche & Anyakoha, 2018;Enemarie et al, 2019). Basic science and technology subjects refer to a set of foundational educational disciplines that encompass fundamental scientific and technological concepts and principles (Nwosu et al, 2022). These subjects according to Odoh et al (2021) are typically taught in primary and secondary schools to provide students with a basic understanding of science, technology, and their applications in the modern world.…”
Section: Introductionmentioning
confidence: 99%